Hydrogen sulfide increases production of NADPH oxidase-dependent hydrogen peroxide and phospholipase D-derived phosphatidic acid in guard cell signaling - Scuffi, Denise (2018)
Hydrogen sulfide (H2S) is an important gaseous signaling molecule in plants that participates in stress responses and development. L-Cys desulfhydrase 1, one of the enzymatic sources of H2S in plants, participates in abscisic acid-induced stomatal closure. We combined pharmacological and genetic approaches to elucidate the involvement of H2S in stomatal closure and the interplay between H2S and other second messengers of the guard cell signaling network, such as hydrogen peroxide (H2O2) and phospholipase D (PLD)-derived phosphatidic acid in Arabidopsis (Arabidopsis thaliana). Both NADPH oxidase isoforms, respiratory burst oxidase homolog (RBOH)D and RBOHF, were required for H2S-induced stomatal closure. In vivo imaging using the cytosolic ratiometric fluorescent biosensor roGFP2-Orp1 revealed that H2S stimulates H2O2 production in Arabidopsis guard cells. Additionally, we observed an interplay between H2S and PLD activity in the regulation of reactive oxygen species production and stomatal movement. The PLDα1 and PLDδ isoforms were required for H2S-induced stomatal closure, and most of the H2S-dependent H2O2 production required the activity of PLDα1. Finally, we showed that H2S induced increases in the PLDδ-derived phosphatidic acid levels in guard cells. Our results revealed the involvement of H2S in the signaling network that controls stomatal closure, and suggest that H2S regulates NADPH oxidase and PLD activity in guard cells.